ANALISIS DAMPAK NEGATIF MINUMAN KERAS DAN JUDI ONLINE DALAM PERSPEKTIF AL-QUR’AN - Sumadi, Eko Sumardianto; Azizah, Alfiyatul; AN, Andri Nirwana; Nugroho, Kharis; Dahliana, Yeti (LPPM STAI Muhammadiyah Probolinggo, 2024)
This study analyzes the negative impacts of alcohol consumption and online gambling activities through a qualitative approach using library research methods, with the Quran and its interpretations as primary sources. Data indicates a significant rise in alcohol consumption and online gambling cases, correlating with increased accidents, violence, liver disease, mental disorders, economic losses, and divorces. The Quran strictly prohibits alcohol and gambling due to their harmful effects on individuals and society. Proposed solutions include strengthening faith and piety, family and community development, strict law enforcement, da’wah and economic empowerment. This research highlights the relevance of the Quran's teachings to modern scientific findings in addressing these social problems. Keywords: Alcohol; Online Gambling; Social Impact; Quran Interpretation.